Genome sequences of five brucella canis strains isolated from different countries throughout the world - Girault, Guillaume; Vicente, Acácia Ferreira [UNESP]; Corde, Yannick; Mioni, Mateus Souza Ribeiro [UNESP]; Keid, Lara Borges; Jay, Maryne; Megid, Jane [UNESP]; Mick, Virginie (American Society for Microbiology, 2018)
Canine brucellosis is a major underestimated zoonosis that remains endemic in many areas of the world. A recent phylogeographic investigation including 53 Brucella canis field isolates revealed the existence of two major lineages worldwide. Here, we report genome sequencing of 5 representative isolates of different clades identified in this study.